Aktivitas Biologis Rimpang Kencur terhadap Lalat Buah Melon II. Bioaktivitas Ekstrak Metanol Rimpang - Edhi Martono (Universitas Gadjah Mada, 1998)
Kumchura (Kaempferia galangal L.) rhizome has been known to posses bioactivity to melon fly in its crude form. Extract preparation from the same plant part was tested against melon fly Bactrocera cucurbitae Coquillet’s eggs and larvae to investigate its toxicity and activity. Toxicity test was done by diluting the rhizome’s methanolic extract and incorporating the solution to larval diet. Based on the toxicity test, sublethal concentrations were then tested to determine the extract activity to egg and larval survivals, larval stage duration, puparial weight and length, extracts’ repellency to larvae and extracts’ hormonal activity to larvae. The result showed that kumchura extract toxicity was only considered “slightly toxic”, but sublethal concentration as low as 0.3125% (to eggs) and 2.5% (to larvae) significantly affected the fly’s survival, while the same concentration to egg and 0.625% concentration to larvae significantly prolonged larval stage durations. Extracts’ repellency to larvae was siginificant in sublethal concentration as low as 0.3125%, but kumchura extract has no significant effect on puparial weight and length, and did not contain any hormonal activities toward melon fly.